The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1617/s11527-016-0809-5
|View full text |Cite
|
Sign up to set email alerts
|

New additions for eco-efficient cement design. Impact on calorimetric behaviour and comparison of test methods

Abstract: The pursuit of new alternative construction materials has intensified substantially in recent years due to the economic, technical and environmental benefits deriving from their use. The study of the effect of such materials on heat of hydration is of particular importance, for any rise in that parameter may shorten the service life of concrete structures considerably. This paper describes an in-depth study of including clay-based sanitary ware (SW) and construction and demolition (CDW) waste as active additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
4
10
1
1
Order By: Relevance
“…The data showed lower maximum heat in the mortars containing granite quarry dust than in the reference: 5.5 % lower in OPC+10%AF and 19.3 % lower in OPC+20%AF. Similar behaviour has been reported for other pozzolanic materials included in new cements at similar replacement ratios, such as paper mill sludge [73], fly ash [74], fired clay-based sanitary ware [15] and milled ash [29].…”
Section: Heat Of Hydrationsupporting
confidence: 81%
See 1 more Smart Citation
“…The data showed lower maximum heat in the mortars containing granite quarry dust than in the reference: 5.5 % lower in OPC+10%AF and 19.3 % lower in OPC+20%AF. Similar behaviour has been reported for other pozzolanic materials included in new cements at similar replacement ratios, such as paper mill sludge [73], fly ash [74], fired clay-based sanitary ware [15] and milled ash [29].…”
Section: Heat Of Hydrationsupporting
confidence: 81%
“…That has left a large scientific-technical gap in the understanding of other properties associated with material durability, such as: i) indirect indicators of transport intensity (water absorption, capillarity and electrical resistivity) [12]; ii) volume change resulting from drying shrinkage or early-age swelling that may induce micro-or macrocracking, compromising service life [13]; iii) the alkali-silica reaction due to the simultaneous presence of moisture, reactive silica and cement-borne alkalis, forming silica gel and subsequently map-like cracking [14]; and iv) the heat released during hydration, possibly generating steep thermal gradients that may prompt cracking, a major concern in structures requiring large volumes of concrete such as dams [15].…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…Fired clay industry waste is one of the new pozzolans explored by researchers. A number of prior studies on this material showed that fired clay of different origins has very promising pozzolanic properties because when fired at temperatures of 600°C‐900°C and ground to cement fineness, initially inert clay minerals acquire substantial pozzolanicity . The evaporation of chemically combined water at such temperatures and the resulting breakdown of the crystalline network of clay constituents induces the formation of an amorphous or vitreous material.…”
Section: Introductionmentioning
confidence: 99%
“…Por este motivo, el empleo de cementos con bajo contenido de Clinker, el uso de adiciones provenientes de desechos industriales y la incorporación de áridos reciclados, son acciones que permiten lograr sostenibilidad en la industria. (Medina et al, 2016;Sadiqul Islam et al, 2017).…”
Section: Introductionunclassified